How Effective Is Auditory–Verbal Therapy (AVT) for Building Language Development of Children with Cochlear Implants? A Systematic Review - Paris Binos; Elina Nirgianaki; George Psillas (Life, 2021)
This systematic review sheds light on the effectiveness of auditory–verbal therapy (AVT) outcomes in children with cochlear implants (CIs). The presented outcome is based on research findings from the last 10 years. The systematic review was designed based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and Critical Appraisal of Treatment Evidence (CATE) checklist. Specific keywords were chosen based on the research question and searched on the PubMed database. All searched papers were analysed based on specific exclusion criteria and classified into four evidence levels. The results revealed that children who participated in AV therapy can achieve linguistic skills at the same level as their hearing peers. Voice quality seemed positively affected, placing young children with CIs in the normal range for receptive vocabulary development. In contrast, reading skills seemed less benefited. AV therapy seems to contribute to integration into mainstream society. Despite the recorded speech and language improvements of young children with CIs, the aim of AV therapy is still not fulfilled. AV therapy can be seen as the best clinical practice for young children with CIs till now, but the lack of well-controlled studies is undermining.